Ulayat Land Registration in Providing Legal Certainty through Certification Based on the Principle of Justice - Nova Yarsina; Ari Budianto; Marsiansyahd; Dian Arfianto (PT. Islamic Research Publiser, 2026)
The registration of ulayat (customary communal) land remains a critical issue in Indonesia’s agrarian governance, particularly in relation to ensuring legal certainty while respecting the rights of indigenous communities. This study aims to examine the legal framework and implementation of ulayat land registration as a mechanism for providing legal certainty through certification based on the principle of justice. The research employs a normative juridical approach combined with a socio-legal perspective by analysing statutory regulations, legal doctrines, and relevant case practices concerning customary land rights within the Indonesian land administration system. The findings reveal that although national land regulations formally recognise the existence of ulayat rights, their registration and certification processes remain limited due to normative ambiguities, administrative constraints, and inconsistencies in recognising customary communities. As a result, many indigenous communities experience difficulties in obtaining formal legal protection for their communal land. The study further shows that a justice-based certification model—one that integrates recognition of customary institutions, participatory mapping, and adaptive regulatory mechanisms—can strengthen legal certainty while safeguarding communal ownership values embedded in customary law. This research contributes to the development of agrarian law and socio-legal scholarship by proposing a justice-oriented framework for ulayat land registration that harmonises state land administration with customary legal principles. The study also offers policy recommendations for improving regulatory coherence and institutional coordination to enhance the protection of indigenous land rights and promote equitable land governance.